A geografia do futebol brasileiro : esporte e relações político-econômicas - Souza, Wesley Ferreira de (2017)
Since soccer?s arrival in Brazil on the 19th century, either through schools, either through people involved with it, as Charles Miller for example, many changes in its organization have occurred, although many old practices have persisted. During this period, it became popular, democratic and professional, changes that almost always place in opposite sides the elite and the people, professional and amateur, field and arena, besides other antagonisms that arise from the conflicts that emerge from these disputes. Either the community fields, a place where people who could not attend official clubs or who sought to play soccer for fun, or the clubs, neither one has escaped from this adjustment to current soccer. Our organization structure concentrated in the states, besides the championships and the clubs relationships with their locality and economy, is also part of a process in which groups have disputed for power in soccer. Even reflecting what happens at the Brazilian society, with many social and economic problems, soccer represents to a significant portion of the population, a way of cultural expression. Our concern focus on soccer elitism, surrounded by giant financial transactions, and that distances itself more and more from its crowd. This is the event that we study here, and how it reflects on the geographic space organization